Violence, Insecurity and Hybrid Organizational Forms: A Study in Conflict-ridden zones in Colombia (2010)
We study organizational forms in conflict-ridden zones of rural Colombia and analyze the impact of violence and subjective perceptions of insecurity on the choice of hybrid organizational modes. Based on a survey of 743 rural producers in five geographical regions, we find that the perceptions of personal and political insecurity correlate positively with hybridization in the organization of production and that the perception of personal insecurity correlates positively with the hybridization in the organization of distribution. Objective measures of violence also correlate positively with the degree of hybridization: the homicide rate is related to hybridization in distribution, and displaced population is related to hybridization in production. The distinction between the organizational forms of production and distribution appears to be important, since the determinants of hybridization substantially differ between these two activities.